Receptor tyrosine kinases and drug resistance: development and characterization of in vitro models of resistance to RTK inhibitors. - O'Driscoll, Lorraine (My University, 2015)
Aberrant expression of receptor tyrosine kinases (RTKs) has been extensively associated with alterations in the physiological activities of cells. These include cell growth and differentiation, cell death/survival, and the motility of cells which can subsequently lead to emergence of various diseases including cancer. Recent advances in the treatment of cancer have involved using RTKs as therapeutic targets. Unfortunately, the clinical use of receptor tyrosine kinase inhibitors (RTKIs) for the treatment of cancer has been hindered by innate or acquired resistance among some patients, as also experienced with classical chemotherapy. It has become apparent that the deregulated expression of RTKs may play a signifi cant part in driving this resistance. In order to fully elucidate the role of RTKs in drug resistance, the use of preclinical models has helped to mimic this clinical problem. In this chapter, we describe the methods associated with establishing and characterizing cell line models of drug resistance to the dual RTKI, lapatinib. These methods include the assessment of lapatinib resistance; cross-resistance to other RTKIs; the alteration of RTK expression; and other associated phenotypic changes such as cellular migration, invasion, and anoikis sensitivity/resistance.
Meth. Mol. Biol.
PUBLISHED
Keywords: RTKIs; Drug resistance; Cell line models; Phenotypic changes; Cross-resistance; Motility; Invasion; Anoikis; RTK protein expression; Cancer; CANCER